Preparation of branched canola protein isolate and effects of molecular architecture on solution flow properties. (June 2017) - Li, Shuzhao; Donner, Elizabeth; Thompson, Michael; Zhang, Yachuan; Rempel, Curtis; Liu, Qiang
Abstract: Two branched canola protein isolates (CPI) with different branching degree were prepared using bis-epoxide as a chain extender. It was found that the branching reaction may take place in any protein fraction in native CPI; furthermore, by increasing the amount of chain extender, more native protein chains in CPI were coupled to form branches. In the study of flow properties of native and branched CPI solutions, it was found that the apparent viscosities of two branched CPI remarkably increased compared to that of native CPI over all concentrations tested. At 22 °C and pH 7, native CPI solution showed slight shear thinning behavior with the increase of shear rate; however, shear thickening was observed at low shear rate for branched CPI. Furthermore, shear thickening was more pronounced with the increase of branching degree and concentration of branched CPI solution. Shear thinning behavior of native CPI became marked at pH 11; however, the shear thickening property of branched sample was weakened at high pH. The novel findings in flow properties of the branched CPI solution could be potentially applied in the food industry, such as increasing foaming property and gelling ability of food products. Highlights: Branched CPI was obtained by intermolecular instead of intramolecular coupling. Branched CPI solution showed higher viscosity than native and shear thickening. Viscosity of branched CPI solution had lower thermal dependency than native CPI. High pH strengthened shear thinning of native CPI. High pH weakened shear thickening of branched CPI.